Legal Protection for Property Tenants Against the Sale of Rented Property by the Owner to A Third Party - I Nyoman Sukarna Wijaya; I Nyoman Budiana (PT ARRUS Intelektual Indonesia, 2026)
The transfer of ownership of a property still under lease often gives rise to disputes between the tenant and the new buyer. The main issue lies in the legal status of the lease agreement after the leased object is transferred and the extent of legal protection provided to the tenant. This article aims to analyze the legal status of the lease agreement after the transfer of ownership and examine the judge's considerations in Decision Number 1127/Pdt.G/2022/PN.Dps. This research is a normative juridical study with a statutory and conceptual approach. The primary legal materials are the Civil Code and court decisions, while the secondary legal materials come from relevant journals and legal literature as stated in the research manuscript. The results of the study indicate that based on Article 1576 of the Civil Code, the sale of a leased object does not terminate a previously established lease relationship, unless otherwise agreed. The Panel of Judges declared Lease Agreement No. 01 dated January 3, 2018, valid and binding and provided legal protection in the form of fulfillment of the agreement. This decision reflects the application of the principles of pacta sunt servanda, the principle of good faith, and the theory of preventive and repressive legal protection. Normatively and theoretically, protection for tenants is a manifestation of legal certainty, justice, and benefit in the practice of property agreements in Indonesia.